Analysis of Food Consumption Patterns with the Incidence of Type 2 Diabetes Mellitus in Kulon Progo D.I, Yogyakarta. (Public Health Perspective Journal, 2020)
Diabetes Mellitus Type 2 is a pathophysiological disorder of insulin resistance. Coverage of type 2 diabetes mellitus in Yogyakarta Special Region 2017 (8,321 cases). In Kulon Progo Regency 2016 (1,355 cases), 2017 (1,235 cases), 2018 (1,532 cases). The purpose of the study was to analyze food consumption patterns with the incidence of type 2 diabetes mellitus in the Kulon Progo Regency, a special area of Yogyakarta. The study used a case-control study design. The research sample of 114 respondents was obtained by purposive sampling technique. Data collection techniques are interviews, observation, questionnaire. Data analysis in the study used the Chi-Square test and test logistic regression. The results of the study found that there was an influence on the variable of dietary consumption (p = 0,000) on the incidence of type 2 diabetes mellitus in the Kulon Progo district of Yogyakarta. The most influential variable is the pattern of eating consumption with p = 0,000; EXP (B) / OR = 0.004. So it is necessary to pay attention again to one's lifestyle in terms of diet, increase counseling at all levels of society both who already suffer from diabetes mellitus or do not suffer from diabetes mellitus.